2022
DOI: 10.3390/nano12183188
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Applications and Biological Impact of Nanocellulose

Abstract: Interest in cellulose-based nanomaterials has continued to increase dramatically in the past few years, especially with advances in the production routes of nanocellulose—such as cellulose nanocrystals (CNC), cellulose nanofibrils (CNF) and bacterial nanocellulose (BNC)—that tailor their performances [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Cellulose nanofibers (CNFs) exhibit distinct features, including mechanical strength, porosity, high water retention, high surface functionality, and an entangled fibrous network. These traits play a crucial role in determining the attributes of the resulting templated materials [28]. The use of templating with CNFs has been extensively investigated across a range of applications, including catalysis, batteries, supercapacitors, electrodes, building materials, biomaterials, and membranes [29].…”
Section: Id Template-assisted Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Cellulose nanofibers (CNFs) exhibit distinct features, including mechanical strength, porosity, high water retention, high surface functionality, and an entangled fibrous network. These traits play a crucial role in determining the attributes of the resulting templated materials [28]. The use of templating with CNFs has been extensively investigated across a range of applications, including catalysis, batteries, supercapacitors, electrodes, building materials, biomaterials, and membranes [29].…”
Section: Id Template-assisted Synthesismentioning
confidence: 99%
“…These attributes render them highly appropriate for sustainable textile applications [66]. Added to that, it has been shown that the use of nanocellulosebased coatings may provide effective protection against ultraviolet (UV) radiation for textiles, hence safeguarding them from the detrimental effects of UV radiation [28]. The distinctive characteristics shown by nanocellulose, including its exceptional mechanical strength, biocompatibility, and customizable surface chemistry, render it a very suitable substance for the development of UV-resistant coatings in the realm of sustainable textiles.…”
Section: Iid Uv-resistant Coatingsmentioning
confidence: 99%